Tinjauan Yuridis Terhadap Pelaku Penelantaran Anak Berdasarkan Undang-undang Perlindungan Anak - I Putu Gede Fajar Riski Andika; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Child neglect is a phenomenon that often occurs in society which means that adults fail to take responsibility for providing various needs or adequate needs for the child. This can be seen from the needs such as clothing, food, shelter, education to the health of the child himself. This study aims to examine the legal protection of children who are victims of neglect and uncover criminal sanctions against perpetrators of neglect of children. This study uses a normative method considering that there is still a lack of legal norms, with a legislative approach. The data sources used are primary and secondary data obtained through library or recording techniques. After the data is collected, it is then processed descriptively qualitatively. Legal protection for neglected children is a right for every citizen, especially children, which can be divided into preventive and repressive protection. Law Number 35 of 2014, regulates various matters relating to the protection of children about what is prohibited until the sanctions in Article 76B contain that all forms of exploitation such as neglect and involving children in bad or wrong conditions can be subject to the threat of punishment as stated in Article 77B sentenced to imprisonment for 5 years or a fine of up to IDR 100,000,000.